MANAJEMEN LAYANAN SUMBER DAYA MANUSIA DALAM PENGAJUAN DISPENSASI KAWIN DI ERA PANDEMI COVID -19 - Utami, Sri Daryati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Human resource service management very needed in the education unit especially the era of the corona virus 19 pandemic.Especially when there are students who have get merried early because of economic factor or because pregnant out of wedlock. So the education units must be able to provide solution and provide opportunities to keep warning for students. But if they fell les comfortable then they can apply for study in the package B (Kejarpaket B). The purpose of this research (1) To analyze Human resource service management in the era of the corona virus 19 pandemic (case study in SMPN 3 Mojokerto). (2) To analyze the implications Human resource service management in applying for dispensation for mirage in the era of the corona virus 19 pandemic. The type of this research is qualitative with the case study approach, with the techniques of collecton data through observation, interview and document. The result of research Human resource service management in applying for dispensation for mirage in the era of the corona virus 19 pandemic in SMPN 3 Mojokerto are, (1) The students are allowed to apply for marriage dispensation if they are already pregnant (2) The students are allowed to apply for marriage dispensation are given assistance from education actors (3) In order to be able to continu learning, the students are directed to take part in the program Package “B” (kejarpaket B).